Synthesis of exopolysaccharide ethapolan during сultivation of auxotroph Acinetobacter sp. IMV B-7005 in the medium with sunflower oil - Ivahniuk, Mykola; Pirog, Tatiana; Penchuk, Yuri (My University, 2014)
The possibility to use the multivitamin complex «Complevit» as a source of calcium pantothenate by auxotrophic strain Acinetobacter sp. IMV B-7005 – the producer of microbial exopolysaccharide ethapolan was shown. The cultivation conditions for the producer were established to provide the synthesis of 6.6-6.7 g/l of the desired product in the medium with high (4-5 %) content of sunflower oil – cheap and available substrate for microbial technologies.
Keywords: кафедра біотехнології і мікробіології; еxopolysaccharides; sunflower oil; growth factors; calcium pantothenate; intensification of biosynthesis; экзополисахарид; подсолнечное масло; факторы роста; пантотенат кальция; интенсификация биосинтеза; екзополісахарид; соняшникова олія; фактори росту; пантотенат кальцію; інтенсифікація біосинтезу